Molecular mechanisms, pathophysiology and laboratory investigations of favism - Kwaifa, Ibrahim Kalle; Moses, Solomon; ALBuwaiqi, Khoula Salim Ali; Abdul, Barka Sanni; Aliyu, Abdullahi (Edelweiss Applied Science and Technology, 2026)
Abstract: Favism refers to a hemolytic episode triggered by consumption of fava bean in person with glucose-6-phosphate dehydrogenase (G6PD) impairment. It is characterized by splenomegaly, anemia, and jaundice. This review describes in detail the molecular mechanisms, pathophysiology, complications, and laboratory investigations of favism. The fava bean contains significant amounts of antinutritional substances, including vicine and convicine, which are responsible for the hemolytic crises observed. Red blood cells with G6PD deficiency are vulnerable to oxidative damage because they lack protection against reactive oxygen species. Hemolysis or erythrophagocytosis of red blood cells can occur when specific agents, such as raw fava beans, sulfonamides, or infections, are activated. However, avoiding raw fava beans can help prevent favism. This is because boiling fava beans has been shown to reduce the negative effects of the antinutritional chemicals vicine and divicine present in the fava beans. G6PD deficiency currently has no treatment. Nonetheless, gene therapy appears to be a promising treatment option for enzyme deficiencies. Data for this research were collected from PubMed, Google Scholar, Springer, Nature, Taylor and Francis, MDPI, BMC, and other related sources.